1978
DOI: 10.1073/pnas.75.8.3703
|View full text |Cite
|
Sign up to set email alerts
|

Detection of an early surface change during oncogenic transformation.

Abstract: Fluorescamine, which can label surface components of cells grown as monolayers in culture, has been used to probe alterations in chicken embryo fibroblasts infected with a temperature-sensitive mutant of Rous sarcoma virus, Prague A, LA24. The fluorescence of bound fluorescamine on cells at the permissive temperature (350) was found to be about 1/3 that of cells cultured at the nonpermissive temperature (410). During development of the transformed phenotype, i.e., after transfer of the cells from 410 to 350, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1

Year Published

1979
1979
2008
2008

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 16 publications
0
8
1
Order By: Relevance
“…This possibility cannot be ruled out at this time. Previous studies with this particular clone of LA24 in our laboratory, however, have shown tight control at 410C for morphology, 2-dGlc uptake, and collagen synthesis in PAT cells (22), and fluorescamine labeling, dThd incorporation, morphology, and 2-dGlc uptake in CEF (29).…”
Section: Resultsmentioning
confidence: 99%
“…This possibility cannot be ruled out at this time. Previous studies with this particular clone of LA24 in our laboratory, however, have shown tight control at 410C for morphology, 2-dGlc uptake, and collagen synthesis in PAT cells (22), and fluorescamine labeling, dThd incorporation, morphology, and 2-dGlc uptake in CEF (29).…”
Section: Resultsmentioning
confidence: 99%
“…Labeling of cells with fluorescamine and analysis of fluorescent products by SDS-polyacrylamide gel electrophoresis: This was carried out as previously described (18). Briefly, 2 ml of labeling solution consisting of 1 mg fluorescamine/0.5% acetone/0.2 Msodium borate, pH 9.0, was added to monolayers.…”
Section: Methodsmentioning
confidence: 99%
“…Alterations which occur as a result of oncogenic transformation have been characterized using a variety of techniques. One that we have developed and used extensively is the reaction of monolayers of cultured cells with fluorescamine (8,9,18,19), a compound that reacts with primary amines to form fluorescent adducts. We have demonstrated that primary and established lines of cells transformed by viruses and a chemical carcinogen exhibit three-to four-fold lower fluorescence intensities than do their nontransformed counterparts (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is the added advantage and flexibility of easily snapping the harness on and off during and after experimental periods, permitting recordings from a number of animals with the same transmitter. [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]1977), In subsequent experiments involving about 400 rats we have investigated how magnitude of remote loss varied with (a) cortical region, (b) size of lesion, (c) time elapsed between lesion and sacrifice, and (d) post-operative environment, either enriched (EC) or impoverished (IC). Somesthetic cortex, although adjacent to the occipital area, showed only about 2% loss of DNA while remaining dorsal cortex and ventral cortex lost 6-8%; hippocampus showed no change.…”
Section: How Plastic Is the Nervousmentioning
confidence: 99%